METODE DE ÎMBUNĂTĂŢIRE A DECIZIILOR MANAGERIALE - USM ADMIN (Moldova State University, 2007)
How can we know the taken decision is a correct one? Which of psycho -pedagogic aspect would be a good one for a decision? These questions have their answers in this article. These questions contains: the criteria of the efficient decision, the manager ̉s actual psychological point of view in the problem of taking the decision, the use of some methods which are good for the management decision, as the decision analysis. This article will serve managers from pre - uni- versity institutions for a support, which will help to have a correct selection of the work techniques, in such a way the taken decision to be useful.